The Effect of Investment and Minimum Wages on Labor Absorption For Small Industry in Gowa District - Mita; Sabir; Fitrianti, Retno (Economics and Business Journal (ECBIS), 2023)
The Effect of Investment and Minimum Wage on Employment of Small Industry in Gowa Regency. This study aims to determine the effect of investment and minimum wages on the absorption of small industrial workers in Gowa Regency in the 2016-2020 period. The type of research used in this study is descriptive quantitative. The data used is secondary data obtained in ready-made form from the Department of Industry and Trade (DISPERINDAG) and the Department of Manpower and Transmigration (DISNAKERTRANS) during 2016-2020. The data analysis technique in this study is multiple regression analysis using SPSS. Based on the results of multiple regression analysis, it can be concluded that investment has a positive and significant effect on employment in the industrial sector and the minimum wage has a positive and insignificant effect on employment.